OBP fused with cell-penetrating peptides promotes liposomal transduction - Gonçalves, Filipa D. (2018)
Cell-penetrating peptides (CPPs) have been applied as novel transport systems with the ability to facilitate the delivery of peptides, proteins, and oligonucleotides into cells. Herein, we designed different fusion proteins composed by pig odorant binding protein (OBP-I) and three CPPs, namely Tat, pVEC and Pep-1. A new methodology using liposomes as reservoirs and OBP:CPPs as carriers was developed as an advanced system to capture odorant molecules. 1-aminoanthracene (1-AMA) was used as a model molecule to evaluate the transduction ability of OBP:CPPs into the reservoirs. The transduction efficiency was dependent on the initial capacity of OBP:CPPs to bind 1-AMA and on the penetration of liposomes promoted by the CPPs. An encapsulation efficiency of 42% was obtained with OBP:Tat fusion protein. The presence of Tat peptide increased the 1-AMA transduction of 1.3 and 2.5 fold compared with Pep-1 and pVEC, respectively. This work expands the application of OBPs and CPPs on the design of promising capture and delivery systems for textile and cosmetic applications.